2019
DOI: 10.1111/all.13771
|View full text |Cite
|
Sign up to set email alerts
|

Precision medicine for the discovery of treatable mechanisms in severe asthma

Abstract: Although the complex disease of asthma has been defined as being heterogeneous, the extent of its endophenotypes remains unclear. The pharmacological approach to initiating treatment has, until recently, been based on disease control and severity.The introduction of antibody therapies targeting the Type 2 inflammation pathway for patients with severe asthma has resulted in the recognition of an allergic and an eosinophilic phenotype, which are not mutually exclusive. Concomitantly, molecular phenotyping based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 53 publications
0
85
0
2
Order By: Relevance
“…The elucidation of the genetic variants associated with NSAIDs hypersensitivity could help us prevent and evaluate potential risks through genetic testing, guiding precision medicine. 29,[173][174][175] However, despite recent advances, including high-throughput sequencing technologies development, individual predisposing factors remain unknown. 176 In addition to the difficulties to shed light on the genetics of complex diseases, another important drawback in NSAIDs hypersensitivity is the heterogeneity of phenotypes, and potential differences in their definition.…”
Section: On the Genetics Of Nsaids Hypersensitivitymentioning
confidence: 99%
“…The elucidation of the genetic variants associated with NSAIDs hypersensitivity could help us prevent and evaluate potential risks through genetic testing, guiding precision medicine. 29,[173][174][175] However, despite recent advances, including high-throughput sequencing technologies development, individual predisposing factors remain unknown. 176 In addition to the difficulties to shed light on the genetics of complex diseases, another important drawback in NSAIDs hypersensitivity is the heterogeneity of phenotypes, and potential differences in their definition.…”
Section: On the Genetics Of Nsaids Hypersensitivitymentioning
confidence: 99%
“…Another perspective from omics sciences is the rising concept of "treatable mechanisms" to replace phenotypes. Indeed, omics sciences have highlighted numerous up-or downregulated pathways that represent potential robust biomarkers bearing enough precision necessary for 4P medicine to better model asthma and provide "care and cure" at the level of a single patient and thus move from dissociated fingerprints to integrative handprints (Figures 1, 4) (99,100). Though, one must bear in mind that omic (i.e., molecular phenotype) approach provide association between phenotype and molecular pathways.…”
Section: Future Directions: From Omics To "Treatable Mechanisms"mentioning
confidence: 99%
“…ARDS, as defined by the Berlin criteria, 16 is a heterogeneous syndrome, and each patient is a unique case. Personalized or precision medicine is expanding in multiple domains of medicine, [17][18][19] including the identification of ARDS subphenotypes that may respond differently to treatments. 20 Another theoretical example is the recent re-analysis of the ART trial, 21 identified with cluster analysis.…”
Section: Management Of Severe Ards: New Strategies and Ongoing Challementioning
confidence: 99%